Capital Structure and Financial Performance of Retail Firms: Empirical Evidence from South Africa: Array - Mukaddam, Shaa’ista; Sibindi, Athenia Bongani (Acta Universitatis Danubius. Œconomica, 2020)
Capital structure has been a subject of debate for a number of decades. Extant studies have tried to test the various theories of capital structure. The most notable theories are the Modigliani and Miller capital structure irrelevance propositions; the trade-off, and the pecking order theories. Therefore, due to inconclusive findings in earlier studies this paper attempted to determine the relationship between capital structure and financial performance within the retail industry in South Africa. The wholesale and retail sector accounts for a large portion of South Africa’s Gross Domestic Product, which signifies that the retail sector is worth exploring in order to obtain an overview of their capital structure and financial performance. This study employed as sample of 18 South African firms in the wholesale and retail sector listed on the Johannesburg Securities Exchange. The data was extracted for a ten-year period ranging from 2010 to 2019. Panel data econometric techniques were used to conduct the analysis. The study found a negative relationship between capital structure and financial performance of South African retail firms. The findings were consistent with the pecking order theory that predicted a negative relationship between debt and financial performance. Therefore, it can be inferred that the profitability of retail firms in South Africa is not a function of how much debt firms have accumulated. The current debt levels in this sector negatively influenced financial performance. This finding was in alignment with the pecking order theory of financing behaviour as opposed to the trade-off theory of financing behaviour.